Modernitas dan Tantangannya terhadap Pelaksanaan Dakwah - Asmaya, Enung (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2009)
Modernity is viewed differently in western and eastern/Islamic culture. In western, it is associated more on theissue of secularism, the separation between religious affairs and the state. Another issue is the application of economiccapitalistic system, which concerns with the material life and reduces the spirit of sharing. Besides, the development oftechnology has reduced the quality of interpersonal relationship and has caused worries and psychosomatics. Not allMuslims agree with these issues. However, modernity also gives spirit to the progress of Muslim society. It can make peopleuse their optimal thinking to manage natural resources and their potentials so that they can live much better. For that reason,modernity can be a certain challenge to the Islamic preaching.